381In-hospital mortality for infants with HIE who received therapeutic hypothermia: a propensity score-matched cohort study. (2nd September 2021) - Wollny, Krista; Mohammad, Khorshid; Wood, Stephen; Hicks, Matthew; Skiffington, Janice; Cherak, Stephana J.; Metcalfe, Amy
Abstract: Background: In 2016, the Academic Medical Center Neonatal Encephalopathy Task Force recommended therapeutic hypothermia (TH) as the standard-of-care for hypoxic ischemic encephalopathy (HIE). However, not all infants who meet the criteria for TH receive this treatment. The purpose of this study was to compare the risk of mortality for infants with HIE who did and did not receive TH, after accounting for confounders associated with receipt of TH. Methods: A retrospective cohort study was conducted using the 2016 National Inpatient Sample (NIS), which contains 20% of all hospital discharges in the United States. Infants were included if they were diagnosed with HIE and were eligible for TH. Nearest-neighbor propensity score-matching (1:1) without replacement was performed prior to logistic regression analysis. The average treatment effect of TH was calculated to estimate the odds of mortality. Results: There were 211 infants with HIE who received TH, which is an estimated proportion of 24.8% (95% CI: 20.9-29.1%). Infants who received TH were more likely to have a seizure (p < 0.05), be transferred from another hospital (p < 0.001), and have the highest Risk of Mortality scores (p < 0.05). The odds of mortality were 0.91 (95% CI: 0.85-0.97) for infants that received TH, compared to those who did not. Conclusions: Receipt of TH varied across patient groups and was associated with clinical risk factors. The odds of in-hospital mortality were lower in infants who received TH. Key messages: Infants who received TH had a decreased risk of in-hospital mortality compared to infants who did not receive TH.